The Relationship Between Consumption of Blood-Added Tablets and Micronutrient Intake with Hemoglobin Levels of Pregnant Woman - Fauziyaha, Rifqi; Puspitasari, Dyah Intan (Newinera Publisher, 2024)
Anemia is one of the nutritional problems that often occur in pregnant women. A preliminary survey conducted at the Sangkrah Health Center in Surakarta City found that the prevalence of anemia in pregnant women in 2022 was 13.5%. The purpose of this study was to determine the relationship between consumption of blood supplement tablets and intake of micronutrients (iron, folic acid, vitamin C and vitamin B12) with hemoglobin levels of pregnant women at the Sangkrah Health Center in Surakarta City. The method used was observational with a cross sectional approach. Analysis of relationship test using chi-square statistical test. The results of this study showed that of the 36 respondents who were obedient in taking blood supplement tablets, 18 respondents (50%) had normal hemoglobin levels and 18 respondents (50%) had low hemoglobin levels and of the 18 respondents who were not obedient in taking blood supplement tablets, 6 respondents (33.3%) had normal hemoglobin levels and 12 respondents (66.7%) had low hemoglobin levels. There is no relationship between adherence to taking blood supplement tablets and hemoglobin levels (p=0.245), there is a relationship between iron intake and hemoglobin levels (p=0.003), there is a relationship between folic acid intake and hemoglobin levels (p=0.004), there is a relationship between vitamin C intake and hemoglobin levels (p=0.019), there is no relationship between vitamin B12 intake and hemoglobin levels (p=0.161).